Extension of Mean Field Theory and General Form of Order Parameter - Mongkolsakulvong, Saman (Agriculture and Natural Resources, 2007)
In this work we study the phase transition of liquid crystal between nematic and isotropic phases by introducing the general form of order parameter, si = a cos2 θi – b, then applying mean field theory (Maier-Saupe Theory) to calculate the free energy of the system, and considering the phase transition. We obtain the values of a and b that satisfy the conditions at the transitions.